The production, function, and clinical applications of IL-33 in type 2 inflammation-related respiratory diseases - Gu, Shiyao; Wang, Ruixuan; Zhang, Wantian; Wen, Cen; Chen, Chunhua; Liu, Su; Lei, Qian; Zhang, Peng; Zeng, Si (Frontiers in Immunology, 2024)
Epithelial-derived , as a member of alarm signals, is a chemical substance produced under harmful stimuli that can promote innate immunity and activate adaptive immune responses. Type 2 inflammation refers to inflammation primarily mediated by Type 2 helper T cells (Th2), Type 2 innate lymphoid cells (ILC2), and related cytokines. Type 2 inflammation manifests in various forms in the lungs, with diseases such as asthma and chronic obstructive pulmonary disease chronic obstructive pulmonary disease (COPD) closely associated with Type 2 inflammation. Recent research suggests that IL-33 has a promoting effect on Type 2 inflammation in the lungs and can be regarded as an alarm signal for Type 2 inflammation. This article provides an overview of the mechanisms and related targets of IL-33 in the development of lung diseases caused by Type 2 inflammation, and summarizes the associated treatment methods. Analyzing lung diseases from a new perspective through the alarm of Type 2 inflammation helps to gain a deeper understanding of the pathogenesis of these related lung diseases. This, in turn, facilitates a better understanding of the latest treatment methods and potential therapeutic targets for diseases, with the expectation that targeting lL-33 can propose new strategies for disease prevention.